Application of multi-wavelength technique for photoacoustic imaging to delineate tumor margins during maximum-safe resection of glioma: A preliminary simulation study. (December 2019) - Najafzadeh, Ebrahim; Ghadiri, Hossein; Alimohamadi, Maysam; Farnia, Parastoo; Mehrmohammadi, Mohammad; Ahmadian, Alireza
Highlights: The infiltrative nature of gliomas and their close resemblance to normal brain parenchyma makes it challenging to achieve maximal resection. Our simulation study shown multi-wavelength photoacoustic imaging (MWPAI) could be used for delineation of neoplastic tissue during resection of glioma tumors. The amount of optical absorption for the blood layer is different from others such as normal and tumor tissues and the anatomic region of blood vessels as the most crucial optical absorber is recognizable by using the proper wavelength. As high-grade gliomas are usually associated with a prominent meshwork of angiogenic vessels, this may be a promising finding to delineate the vascular-rich glioma margins during surgery. In the MWPAI, the longer wavelengths are used for evaluation of the deeper tumor margins due to its higher penetration and, the shorter wavelengths are used for margins closer to the surface, due to a higher optical absorption. Abstract: Accurate margin delineation and safe maximal resection of glioma is one of the most challenging problems of neurosurgery, due to its close resemblance to normal brain parenchyma. However, different intraoperative visualization methods have been used for real-time intraoperative investigation of the borders of the resection cavity, each having advantages and limitations. This preliminary study was designed to simulate multi-wavelength photoacoustic imaging for brain tumor margin delineation for maximum safe resection of glioma. Since the photoacoustic signal is directly related to the amount of optical energy absorption by the endogenous tissue chromophores such as hemoglobin; it may be able to illustrate the critical structures such as tumor vessels during surgery. The simulation of the optical and acoustic part was done by using Monte-Carlo and k-wave toolbox, respectively. As our simulation results proved, at different wavelengths and depths, the amount of optical absorption for the blood layer is significantly different from others such as normal and tumoral tissues. Furthermore, experimental validation of our approach confirms that, by using multi-wavelengths proportional to the depth of the tumor margin during surgery, tumor margin can be differented using photoacoustic imaging at various depths. Photoacoustic imaging may be considered as a promising imaging modality which combines the spectral contrast of optical imaging as well as the spatial resolution of ultrasound imaging, and may be able to delineate the vascular-rich glioma margins at different depths of the resection cavity during surgery.